Analysis of the Agro Risks of Import Substitution of the Food Production - ZOBOV, Alexander M.; DEGTEREVA, Ekaterina A.; CHERNOVA, Veronica Yu.; STAROSTIN, Vasily S.; GOLODOVA, Zhanna G. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
The relevance of the study is related to the current conditions of the functioning of the Russian economy. The objective of this article is to study the import substitution in terms of possible agro risks and threats caused by the economic and political situation. The analysis of the statistical data characterizing the import substitution in the food industry showed the inefficiency of the current forms and methods of state support. The main sources of risks of import substitution are defined. The change in the global situation and geopolitical realities, which are exacerbated by the low technical level of equipment and the lack of resources, allowed to ascertain that the goals of import substitution can be achieved only through the modernization of production and the introduction of innovative technologies in the food industry. The methods of modernization proposed in this article will make it possible to form a competitive agro-industrial complex able to provide the domestic demand and export supplies with food products.